#### Answer

$-1$

#### Work Step by Step

RECALL:
The zero-exponent rule states that for any non-zero number $a$,
$a^0=1$
Note that $-2^0$ means "the negative of $2^0$."
Use the zero-exponent rule where $a=-4$ to obtain:
$-2^0=-(2^0)=-1$

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

$-1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.